Inclusive Education and the Development of the Self-Concept Concerning Mathematical Competences - Sarah Wieckert (Journal of Systemics, Cybernetics and Informatics, 2021)

(untitled)
The encouragement of the development of a realistic self-concept of the children in their classes is an important challenge for school teachers worldwide. Children who know about their strengths and weaknesses can work on the competences, which need to be improved, more effectively (Irmler, 2015; Kammermeyer & Martschinke, 2003) As Germany signed the UN Convention on the Rights of Persons with Disabilities (Beauftragter der Bundesregierung für die Belange von Menschen mit Behinderungen, 2018; Vereinte Nationen, 2006) the school system which is characterized by external streaming has to change in order to make inclusive settings of learning possible and create an environment in which heterogeneity is seen as a chance rather than as a problem for learning and teaching (Klemm, 2015; Aichele, 2008). The development of mathematical competences can be seen as one part of the basic skills that should be acquired in primary school (Ministerium für Schule und Weiterbildung des Landes Nordrhein-Westfalen, 2008). To gain an understanding of quantities is important in this context and may be a challenge for students – especially for children with visual impairment (Walthes & Degenhardt, 2016; Csocsán, 2003). This contribution presents a study which focuses on the special time of first-grade when primary school students get to know their new learning environment. In that context a survey takes place in the German county of North-Rhine Westphalia and accompanies children with and without special needs in the field of vision which learn together in inclusive classroom environments. At three times during the school year the students become interviewed about their self-concept concerning mathematical competences as well as are participating in learning assessments in this subject. Furthermore interviews with the math teachers of the students take place in order to get an insight into the way they design math lessons in an inclusive classroom setting. Classroom observations of math lessons complete the triangulative research design in which different groups of people are part of the sample and different research methods are being used (Wieckert, 2013) In this means the study depicts a variety of central topics concerning educational research which implies an interdisciplinary approach to school life and therefore addresses different disciplines which are connected with education (e.g. Mathematics, Pedagogy, Psychology, Rehabilitation Sciences).